Experiment and finite element analysis of asymmetrical hardness induced by quenching in railway wheel. (March 2022) - Tian, Yu; Tan, Zhunli; Wang, Jiong; Wang, Rui; Liu, Yanru; Zhang, Min
Highlights: Thermo-phase wheel modeling provides accurate calculated analysis results for hardness prediction. Quenching process parameters for railway wheel production were optimized based on the modeling analysis. The problem of nonuniform hardness on rim sides were solved in industrialized production using the model. Abstract: Excellent properties of railway wheels are of vital significance for adapting to complex and changeable operating environments to reduce maintenance costs and extend service life. This paper presents the results suggesting that the hardness distribution in wheel rim is of obvious inhomogeneity, especially in areas near and away from the flange as 'on two rim sides', which undoubtedly affects the subsequent use of the wheel, such as eccentric abrasion and peeling. Product properties (hardness of wheels) are determined, to a certain extent, by temperature and microstructure changes caused by relevant parameters during water–air alternate spraying process. It leads to differences in heat transfer between the surface and the medium or internal heat conduction. To fully investigate such a complicated quenching, a thermo-phase modeling of wheel quenching was used with transient heat transfer, phase change and hardness calculation taken into account. It was found that unsynchronized cooling on both sides of the rim alters the phase behavior of bainite and martensite, especially in stage III of spraying. However, as the depth from the tread increases, the hardness difference becomes almost less obvious. In this condition, the angle of spraying becomes the key parameter influencing temperature–time process during cooling. The calculated results reveal that the hardness is gradually unified on two rim sides by adjusting the deflection angle of spraying that was simultaneously applied to the tread and the rim. The effect of the adjustment was verified experimentally through subsequent actual wheel production. The test analysis mode combined with transient thermal simulation model can be used to effectively and rapidly optimize parameters for intelligent heat treatment process.